Individual differences in the temporal progression of motion sickness and anxiety: the role of passengers' trait anxiety and motion sickness history. Issue 8 (3rd August 2021) - Stelling, Dirk; Hermes, Michael; Huelmann, Gerrit; Mittelstädt, Justin; Niedermeier, Dominik; Schudlik, Kevin; Duda, Holger
Abstract: The objective of the study is to show that trait anxiety and motion sickness history are responsible for different temporal progressions of sickness in passengers. The level of inflight anxiety and inflight sickness severity was monitored for 124 passengers in a full-motion cabin simulator during a short-haul flight with four different flight segments. Four groups with different characteristics in trait anxiety and motion sickness susceptibility showed different profiles of inflight sickness development. High trait anxiety was responsible for high inflight anxiety and a constantly high level of motion sickness, while passengers with just a motion sickness history showed an increase in motion sickness severity over time. We suggest that trait anxiety and motion sickness susceptibility interact and have an impact on the temporal progression of inflight sickness severity. The analysis of temporal developments of anxiety and sickness are fruitful for understanding the origins of motion sickness, research and individual treatments. Practitioner summary: In a full-motion cabin simulator study with 124 passengers the level of inflight anxiety and inflight sickness severity was monitored. Trait anxiety and motion sickness history were found to have different impacts on the temporal progression of individual sickness severity. Abbreviations: ANOVA: analysis of variance; AVES: air vehicle simulator; hiA/hiM: group with high anxiety and high motion sickness susceptibility; hiA/loM: group with high anxiety and low motion sickness susceptibility;MSSQ: motion sickness susceptibility scale; loA/hiM: group with low anxiety and high motion sickness susceptibility; loA/loM: group with low anxiety and low motion sickness susceptibility; SPSS: statistical package for the social sciences; SSQ-TS: total score from the simulator sickness questionaire; STAI: state trait anxiety inventory